ARTIFICIAL INTELLIGENCE (AI)-BASED TRAINING AND DEVELOPMENT TO ENHANCE EMPLOYEE PRODUCTIVITY AND PERFORMANCE AND ITS EFFECT ON PURCHASE DECISIONS AT CV CAPTION MEDIA DIGITAL - Ranny Fitria Puspitasari; Arief Noviarakhman Zagladi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the role of Artificial Intelligence (AI)-based training and development in enhancing employee productivity and performance and its subsequent effect on purchase decisions at CV Caption Media Digital. The research employs an exploratory sequential mixed-method design, combining qualitative and quantitative approaches. The qualitative phase explores AI-based training practices, while the quantitative phase involves 96 respondents selected using the Bernoulli formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that AI-based training significantly improves employee productivity and performance through personalized learning, real-time feedback, and adaptive training systems. Furthermore, employee productivity and performance have a positive and significant effect on purchase decisions, both individually and simultaneously. The findings reveal that the integration of AI in training not only enhances internal organizational capabilities but also contributes to improved customer satisfaction and stronger purchase decisions. This study provides theoretical contributions to the resource-based view and dynamic capabilities theory, while also offering practical implications for organizations in leveraging AI to improve human resource quality and business outcomes.